Barriers to timely nutritional intervention in ICU patients: exploring predictive factors and neuroendocrine regulatory pathways - Liu, Jiali; Xu, Yali; Xu, Yun; Chen, Jiawen; Duan, Jianfeng; Cheng, Minhua; Yu, Wenkui (Frontiers in Nutrition, 2025)
To elucidate determinants of suboptimal early nutritional support achievement in critical illness. 403 adult ICU patients receiving nutritional support during days 1–7 of admission were enrolled in this retrospective study. For patients, basic patient information, disease severity, inflammatory indicators, and prognostic indicators were collected to explore the reasons for the poor rate of early nutritional support. In addition to observing ICU patients, adult male SD rats were injected with LPS dissolved in saline (10 mg/kg) via a single intraperitoneal injection to simulate the inflammatory state caused by human infection. Skeletal muscle tissues and hypothalamic tissues of rats at different time point (6, 12, and 24 h) s were taken for methylation assay, respectively. The baseline APACHE II (24.45 vs. 21.17, p < 0.001) and CRP (126.44 vs. 88.00 mg/L, p < 0.001) were significantly higher in the non-achieving group (failed to meet 80% target calories by day 7) than in the target-achieving group. Inverse correlations existed between caloric delivery and inflammatory markers (WBC: r = −0.313; CRP: r = −0.311). Septic rats exhibited time-dependent hypothalamic promoter methylation changes absent in skeletal muscle. Systemic inflammation and disease severity constitute primary barriers to nutritional target achievement, potentially mediated through central epigenetic regulation.